2017
DOI: 10.18203/2349-3291.ijcp20170705
|View full text |Cite
|
Sign up to set email alerts
|

To study the clinical profile of dengue fever and to evolve a prognostic marker based on hematological parameters for severe dengue

Abstract: Background: Dengue fever is endemic to most parts of India and the clinical recognition of progression to severe dengue may become difficult in the absence of classical findings. Early recognition of shock or hemorrhage and appropriate management with fluids prevents morbidity/mortality to a great extent. In this study, we attempted to evolve a simple hematological prognostic marker for prediction of severe dengue.Methods: This retrospective descriptive study of 67 children was conducted in the Paediatric Depa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…Monocytosis along with thrombocytopenia is an early and consistent guide in diagnosis of Dengue and a marker of severe Dengue. 17 Eosinophilia (>6%) was observed in 5% of the cases in this study in accordance with few studies. 13,18 However, other studies have shown a higher proportion of cases with eosinophilia.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Monocytosis along with thrombocytopenia is an early and consistent guide in diagnosis of Dengue and a marker of severe Dengue. 17 Eosinophilia (>6%) was observed in 5% of the cases in this study in accordance with few studies. 13,18 However, other studies have shown a higher proportion of cases with eosinophilia.…”
Section: Discussionsupporting
confidence: 92%
“…Neutrophil counts are used as an indicator of acute dengue. 17 Monocytosis (≥10%) was noted in 5% of cases in the study. Few studies had a higher proportion of cases 13,17 .…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations